OBSERVATIONS OF CETACEAN STRANDINGS IN LIMA AND CALLAO, PERÚ: 2016-2022 - Pizarro-Neyra, Jose (2022)
Observations are reported on fourteen specimens of stranded cetaceans in the Lima and Callao regions, central coast of Peru, during September 2016 and July 2022. The species were identified as: Megaptera novaeangliae (Borowski, 1781), Balaenoptera edeni Anderson, 1879, Physeter macrocephalus Linnaeus 1758, Globicephala macrorhynchus Gray 1846, Ziphius cavirostris Cuvier, 1823, Tursiops truncatus (Montagu, 1821) and Phocoena spinipinnis Burmeister 1865. The evidence of interaction of some of the cetaceans with fishing and details of each stranding are reported. The species with the most stranded specimens were P. spinipinnis and M. novaeangliae.